Factors influencing T cell activation and programmed death 1 expression in HIV-infected children. - Prendergast, A; O'Callaghan, M; Menson, E; Hamadache, D; Walters, S; Klein, N; Goulder, P (2012)
Immune activation is the best marker of HIV disease progression in both adults and children. However, the factors that drive immune activation in HIV-infected children remain incompletely understood and may differ from those in adults. Immune activation was investigated in a cohort of 93 untreated HIV-infected children, of median age 10.8 years, and 37 HIV-uninfected children. CD8(+) T cell activation, which was higher in HIV-infected than HIV-uninfected children (p<0.001), did not correlate with viral load (R=-0.03, p=0.838). Similarly, programmed death 1 (PD-1) expression on CD8(+) T cells, which was higher in HIV-infected children than HIV-uninfected children (p<0.001), was not associated with viral load (R=0.11, p=0.40), but correlated with CD8 activation (R=0.41, p=0.002). Both CD8 activation and PD-1 expression were partially driven by the magnitude of the HIV-specific CD8(+) T cell response. CD3(+)CD4(+)CD25(hi)FoxP3(+) regulatory T cells (Tregs) were depleted in HIV-infected, compared to HIV-uninfected, children [median 1.0% (IQR 0.6, 1.9) vs. 2.6% (IQR 1.7, 3.2) CD3 cells; p<0.001]. Depletion was associated with increased CD8 activation (R=-0.27, p=0.068), suggesting that the decline in Tregs may allow immune activation to increase. Taken together, immune activation and PD-1 upregulation in children are not directly driven by viral load but may be influenced by the magnitude of the immune response to HIV itself, and to the depletion of Tregs that occurs during HIV infection. Further understanding of the factors that drive immune activation in children is critical to developing future therapeutic strategies in this population.